(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2020)
Corporate Volunteering (CV) has grown in recent years, looming largely on the agenda of many companies and Civil Society Organizations (CSOs) both internationally and in Uruguay. The objective of this article is to identify the organizational factors that contribute to the management and development of CV and to analyze the articulation between, on the one hand, the theory underpinning the guides published by organizations that promote CV, and on the other, the practices of Uruguayan companies, in order to determine the relevance of the latter as inspiring models of good practice for other companies. To this end, on the one hand, an exhaustive review of CV and CSR guides from Europe and America was carried out, and then a sample of ten guides was selected for thus study; and on the other, a comparative analysis was carried out of four case studies of Uruguay-based companies: Pronto!, Carle & Andrioli, Telefónica, and Sabre. The methodological design entailed a mixed approach for the analysis of the companies and exploration of secondary information sources, with documentary analysis for the CV guides dimension. Among the main organizational factors identified are: the development of strategic CV, the support of leadership and management, CV integrating and promoting the organizational culture of the company, the promotion of volunteer participation, adequate implementation of internal and external communication, inclusion of other stakeholders, and synergy between CV and CSR.